Rational or emotional? a study on organic grocery shopping/ Phang Ing @ Grace, Liew Fung Chai - Phang, Ing@Grace; Liew, Fung Chai (Universiti Teknologi MARA Cawangan Sarawak, 2019)
This paper examined organic food purchase intention among Malaysian grocery shoppers. Adopting the Theory of Planned Behaviour and Norm Activation Model, self-interest and pro-social factors were examined. Selfidentity was added to the framework as an additional variable in shaping the purchase intention of organic food and the mediating effects of the NAM were tested. A total of 131 valid responses were collected and analysed using SPSS v.24 and SmartPLS 3.0 software. The results indicated that purchases of grocery organic products are driven by both rational and emotional motives. There were significant impacts of perceived behavioural control, attitude, and personal norm on purchase intention of organic food. Interestingly, the results show that Malaysian shoppers did not use organic food as a mean to show socially desirable behaviours, but rather as a personal norm in which they were aware of the consequences and felt responsibilities to these negative consequences.